Storage of Encapsulated Liver Cell Spheroids at â€“80Â°C after Storage at Liquid Nitrogen Temperatures - Kilbride, Peter; Selden, Clare; Fuller, Barry; Morris, John (Problems of Cryobiology and Cryomedicine, 2015)
N/A